Endogenous business cycles and growth - Klaus Wälde (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
Current explanations why a growing economy necessarily goes through booms and recessions predict countercyclical R&D investment. As this is very controversial from an empirical perspective, a stochastic Poissonmodel of endogenous business cycles and growth is presented where the determinants of the cyclical behaviour of R&D investment are analytically studied. Providing an explicit expression for the expected length of a cycle shows that high frequency fluctuations can indeed be understood by this approach. It is also shown how small technological improvements translate into large aggregate fluctuations.
Keywords: E32; O41; 330; Endogenous fluctuations and growth; Uncertainty under continuous time; Real Business Cycle; Forschung; Investition; Technischer Fortschritt; Stochastisches Wachstumsmodell; Mehr-Sektoren-Modell; Theorie